Development Of Teaching Modules Based On Local Wisdom In Learning Literature Writing For Students In Elementary School Teacher Education Program - Septika, Hety Diana; Ilyas, Mohammad; Prasetya, Kiftian Hady (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research focuses departs from local wisdom arising from the diversity of tribes, ethnicities and religions that are different for each region in Indonesia, thus making Indonesia have a multicultural society according to the attributes of each region, specifically in this study in East Kalimantan. The introduction of local wisdom for prospective teachers at the basic education level is very important as a basis for introducing elements of regional culture and customs in the educator environment. The urgency of this research focuses on the important role of educators in implementing the learning process with local wisdom content in terms of planning modules based on local wisdom. Teaching modules based on local wisdom are intended to introduce East Kalimantan regional culture to prospective educators, especially elementary school teachers. The task of the educator has an important role in implementing the learning process based on local wisdom by using teaching modules. This study aims to determine the steps for preparing local wisdom-based learning modules and to determine the effectiveness of the modules. The research method used is the ADDIE modeling R&D (Research and Development). The results of the research and development were found as follows: (1) The content and local wisdom context of the people of East Kalimantan which are relevant to the material for studying literary writing in teaching literature in elementary schools, (2) the results of validation by media experts on modules based on local wisdom in learning to write literature in learning literature in SD in the very appropriate category, (3) the results of the validation of material experts on modules based on local wisdom learning to write literature in learning literature in SD in the very feasible category, (4) student responses to modules based on local wisdom learning to write literature in learning literature in SD with a decent category.